Claudin-1-Dependent Destabilization of the Blood–Brain Barrier in Chronic Stroke - Sladojevic, Nikola; Stamatovic, Svetlana M.; Johnson, Allison M.; Choi, Jennifer; Hu, Anna; Dithmer, Sophie; Blasig, Ingolf E.; Keep, Richard F.; Andjelkovic, Anuska V. (The Journal of neuroscience, 2019)
Recent evidence suggests that blood–brain barrier (BBB) recovery and reestablishment of BBB impermeability after stroke is incomplete. This could influence stroke recovery, increase the risk of repeat stroke, and be a solid substrate for developing vascular dementia. Although accumulating evidence has defined morphological alterations and underlying mechanisms of tight junction (TJ) changes during BBB breakdown in acute stroke, very little is known about the type of alterations and mechanisms in BBB “leakage“ found subacutely or chronically. The current study examined BBB structural alterations during the “BBB leakage” associated with the chronic phase of stroke in male mice and both genders of humans. We found significant upregulation of claudin-1 mRNA and protein, a nonspecific claudin for blood vessels, and downregulation in claudin-5 expression. Morphological and biochemical as well as fluorescence resonance energy transfer and fluorescence recovery after photobleaching analysis of postischemic brain endothelial cells and cells overexpressing claudin-1 indicated that newly synthesized claudin-1 was present on the cell membrane (∼45%), was incorporated into the TJ complex with established interaction with zonula occludens-1 (ZO-1), and was building homophilic cis - and trans -interactions. The appearance of claudin-1 in the TJ complex reduced claudin-5 strands (homophilic claudin-5 cis - and trans -interactions) and claudin-5/ZO-1 interaction affecting claudin-5 incorporation into the TJ complex. Moreover, claudin-1 induction was associated with an endothelial proinflammatory phenotype. Targeting claudin-1 with a specific C1C2 peptide improved brain endothelial barrier permeability and functional recovery in chronic stroke condition. This study highlights a potential “defect” in postischemic barrier formation that may underlie prolonged vessel leakiness. SIGNIFICANCE STATEMENT Although rarely expressed at the normal blood–brain barrier (BBB), claudin-1 is expressed in pathological conditions. Analyzing poststroke human and mouse blood microvessels we have identified that claudin-1 is highly expressed in leaky brain microvessels. Our results reveal that claudin-1 is incorporated in BBB tight junction complex, impeding BBB recovery and causing BBB leakiness during poststroke recovery. Targeting claudin-1 with a claudin-1 peptide improves brain endothelial barrier permeability and consequently functional neurological recovery after stroke.